(all‐E)‐ and (5Z)‐Lycopene Display Similar Biological Effects on Adipocytes. Issue 5 (27th December 2018) - Fenni, Soumia; Astier, Julien; Bonnet, Lauriane; Karkeni, Esma; Gouranton, Erwan; Mounien, Lourdes; Couturier, Charlene; Tourniaire, Franck; Böhm, Volker; Hammou, Habib; Landrier, Jean‐François
Abstract : Scope: Although about 90% of lycopene in dietary sources occurs in the linear all‐ trans conformation, a large proportion of the lycopene found in human tissues is of the cis ‐isomer type, notably (5Z)‐lycopene. The biological effects of this (5Z) isomer have been under‐researched. The aim of this study is to evaluate some biological functions of (5Z)‐lycopene in adipocytes and to compare them with those of (all‐E)‐lycopene. Methods and results: (all‐E)‐ and (5Z)‐Lycopene displayed strong similarities in global gene expression profile and biological pathways impacted. Peroxisome proliferator‐activated receptor (PPAR) signaling is identified as a major actor mediating the effects of lycopene isomers. Transactivation assays confirmed the ability of both isomers to transactivate PPARγ. In addition, the TNFα‐induced proinflammatory cytokine mRNA expression in 3T3‐L1 adipocytes is reduced by both isomers via a reduction in the phosphorylation levels of p65. Finally, lycopene isomers restore the TNF‐α‐blunted uptake of glucose by adipocytes via a modulation of AKT phosphorylation. Conclusion: These results show that lycopene isomers exert similar biological functions in adipocytes, linked to their ability to transactivate PPARγ. These findings add to our knowledge of lycopene effects in adipocyte biology and point to the possible use of lycopene in the prevention of obesity‐related disorders. Abstract : (all‐E)‐Lycopene is known to be active on adipocyte biology, but data regarding the biological effect of (5Z)‐lycopene remains scarce. In the present study, it is demonstrated that both (all‐E) and (5Z)‐lycopene similarly transactivated PPARγ. Such an effect is associated to an increase of glucose uptake and a decrease of proinflammatory cytokines expression in adipocytes. These observations pave the way for the potential use of the lycopene isomers in the prevention of obesity‐related pathologies.